1974
DOI: 10.1104/pp.53.6.820
|View full text |Cite
|
Sign up to set email alerts
|

The Azolla, Anabaena azollae Relationship

Abstract: This manuscript reports results of initial studies on acetylene reduction by the symbiotic association. It provides evidence that the symbiotic alga is the agent of acetylene reduction and, if acetylene reduction is a valid assay of the ability to fix N,. the site of N, fixation.MATERIALS AND METHODS Azolla plants, nutrient solutions, growth conditions, isolation of the symbiotic algae, and Chl determinations were as described in thr preceding paper (20).Chemicals DCMU was obtained as Diuron from the E. 1. duP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

1976
1976
1986
1986

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 23 publications
1
35
0
Order By: Relevance
“…Acetylene reduction assays were conducted as described previously using a gas phase of 10%o C2H2, 0.03% CO2 in argon (21,23 (24). GS was assayed by both the coupled biosynthetic assay and the transferase assay (27) Figure 1, a through d. While the absorption maxima of the phycobilins from the two free-living blue-greens occur at about 620 nm, those from the symbiotic algae and the association occur at 610 nm.…”
Section: Acetylene Reduction Assays-nitrogenasementioning
confidence: 99%
See 1 more Smart Citation
“…Acetylene reduction assays were conducted as described previously using a gas phase of 10%o C2H2, 0.03% CO2 in argon (21,23 (24). GS was assayed by both the coupled biosynthetic assay and the transferase assay (27) Figure 1, a through d. While the absorption maxima of the phycobilins from the two free-living blue-greens occur at about 620 nm, those from the symbiotic algae and the association occur at 610 nm.…”
Section: Acetylene Reduction Assays-nitrogenasementioning
confidence: 99%
“…Thus it was necessary to find an independent quantitative estimate for the amount of alga in the association. While nitrogenase is unique to the alga (21) its lability makes it unsuitable for quantitation. Chl a/b ratios provided another estimate, but this was based on the absence of Chl b from the alga (20) and was therefore not as sensitive.…”
mentioning
confidence: 99%
“…The rapid growth of this fern and its ease in handling for laboratory studies make this plant particularly attractive as experimental material for study of plant nutrition in a symbiotic system. Relatively little work had been done with this system until Peters and Mayne (4,5) recently made some initial characterizations of the relationship and showed the essential nature of the algae for growth of plants on N-free media.…”
mentioning
confidence: 99%
“…In the intact association, the alga can provide the Azolla plant with its total nitrogen requirement. Previous studies showed that the symbiont contained nitrogenase and was capable of C2H2 reduction, ATP-dependent H2 evolution, and excretion of ammonia (10,11,13).…”
Section: Introductionmentioning
confidence: 99%
“…In the intact association, the alga can provide the Azolla plant with its total nitrogen requirement. Previous studies showed that the symbiont contained nitrogenase and was capable of C2H2 reduction, ATP-dependent H2 evolution, and excretion of ammonia (10,11,13).Although C2H2 reduction is a simple and sensitive assay of nitrogenase activity, C2H2 is not the biologically important substrate, and the assay is an indirect measurement of nitrogen fixation. Since the reduction of N2 to 2NH3 requires six electrons while reduction of C2H2 to C2H4 requires two electrons, a theoretical conversion factor of 3C2H2 reduced per N2 fixed is frequently used in estimating nitrogen fixation from C2H2 reduction assays.…”
mentioning
confidence: 99%